2019
DOI: 10.18203/2320-1770.ijrcog20193510
|View full text |Cite
|
Sign up to set email alerts
|

Mirena: a novel alternative to hysterectomy

Abstract: Background: To study the awareness and efficacy of Mirena (Levonorgestrel intrauterine system) in treatment of abnormal uterine bleeding.Methods: A prospective analytical study was conducted from January 2012 to June 2018 at Smt. Kashibai Navale medical college and general hospital, Pune, Maharashtra, India. Total 30 women between age of 35 to 45 yrs age were included in the study. Mirena was inserted post-menstrually in the operation room under sedation was done. The women were called for follow-up after 1 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…Ninety-two percent of our patients were satisfied with a decrease in bleeding which was better than another study by Parag M. Hangeker et al which reported overall satisfaction of 76%. 8 A total of 4 out of 73 patients i.e., 5.47% needed a hysterectomy. Comparable results were reported by other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Ninety-two percent of our patients were satisfied with a decrease in bleeding which was better than another study by Parag M. Hangeker et al which reported overall satisfaction of 76%. 8 A total of 4 out of 73 patients i.e., 5.47% needed a hysterectomy. Comparable results were reported by other studies.…”
Section: Discussionmentioning
confidence: 99%